Effect Modification of Modifiable Cardiovascular Risk Factors : A Hospital-Based Matched Case Control Study - Defriman Djafri; Monalisa Monalisa; Fauziah Elytha; Rizanda Machmud (Faculty of Public Health, Andalas University, 2017)
This study aims to find the role of modifiable risk faktors toward the association between hypertension and coronary heart disease in RSUP DR. M. Djamil Padang, in 2016This match case control study was conducted from Desember 2014 to April 2015. We studied 171 samples with 1:2 ratio between the case and the control. Samples are collection using simple random sampling by matching the age and sex. Data through the medical record (secondary data) in RSUP DR. M. Djamil. Bivariate analysis showed that hypertension had OR=16,04 (95%CI 5.705-45.12), obesitas had OR=2.53 (95%CI 1.321-4.844), and hyperusrisemia had OR 2.41 (95%CI 1.292-4.516. Multivariate modeling showed that hyperurisemia had a confounder between assosiated hypertension and Coronary heart disease. Multivariate modeling showed hypertension had the highest risk to coronary heart disease. Obesity and hyperurisemia were associated between hypertension and coronary heart disease. Hypertension were considered as determinant of coronary heart disease. People are expected to manage their blood pressure to decrease the risk of coronary heart disease.